Constructivist interpretation, the work of the iuspositivist judge - Montilla García, Martha Coromoto (Frónesis, 2024)
Human civilization on the product of the social life of human beings is governed by legal rules since antiquity, which has always required its realization way of interpretation. Political societies generate law and legal systems that have governed to humanity, in its various stages and their diverse cultures and regions. Interpret is to attribute a sense or meaning to symbols within certain parameters, corresponding to the judge give value to apply them to specific cases. Thus, the interpretation in the context of the right is essential, and it is even more so in the field of constitutional law. The legal operator, and in particular, the judge is never a mechanical applicator of the statement of policy, repeating without contributing anything to the legal system, the interpreter always through constructive interpretation and resolution to the case brings to the legal system and to look for rationality, reasonableness, and justice in the outcome of his interpretive work, to finally translate it into a decision which becomes individualized standard.